Temporal trends and demographic influences on protein-energy malnutrition in China: a comprehensive analysis from 1990 to 2021 - Zhan, Zhouwei; Yu, Erhan; Huang, Rui; Lin, Hui; Yu, Jiami; Wang, Xiaojie; Guo, Zengqing; Chen, Bijuan (Frontiers in Nutrition, 2025)
BackgroundProtein-energy malnutrition (PEM) remains a critical public health challenge, particularly in aging populations and early childhood. Understanding long-term trends in PEM burden is essential for guiding nutritional policy and targeted interventions in China.MethodsData were derived from the Global Burden of Disease (GBD) Study 2021 for the period 1990–2021. Age-standardized incidence, prevalence, mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), years of life lost (YLLs) rate were analyzed using joinpoint regression and age-period-cohort (APC) models to assess temporal trends. Decomposition analysis was employed to attribute changes to population aging, population growth, and epidemiological shifts. Bayesian APC (BAPC) modeling was used to project the PEM burden through 2030 by sex.ResultsIn 2021, PEM resulted in over 22 million incident cases and 213,682 DALYs in China, with males exhibiting higher age-standardized rates across all indicators. A bimodal age distribution was observed, with peaks in children under 5 and adults over 80. From 1990 to 2021, incidence and prevalence increased until 2015 and then declined, while mortality and DALYs steadily decreased, particularly among females. Compared to global trends, China demonstrated greater reductions in age-standardized mortality and DALYs, but a slight increase in incidence. Joinpoint analysis revealed critical shifts in trend periods, with marked rises between 2010 and 2015 and subsequent declines. APC modeling indicated increasing burden among recent cohorts aged ≥5 years, despite improvements in young children. Decomposition analysis showed that population growth and epidemiological change were key drivers of incidence and DALYs, while aging reduced both incidence and prevalence in males but increased prevalence in females. BAPC projections suggest continued reductions in all burden indicators through 2030, with a steeper decline in females, although males are expected to maintain a higher burden.ConclusionsAlthough the overall health burden of PEM in China has improved, rising incidence and prevalence among older adults highlight the need for age- and sex-targeted nutritional interventions. Proactive strategies are essential to sustain progress and address emerging demographic risks.